Cybersecurity in the energy sector: are we really prepared? - Smith, Don C (Journal of Energy & Natural Resources Law, 2021)
21 I Ibid i . 22 See US Department of Homeland Security, 'DHS Announces New Cybersecurity Requirements for Critical Pipeline Owners and Operators' http://www.dhs.gov/news/2021/05/27/dhs-announces-new-cybersecurity-requirements-critical-pipeline-owners-and-operators accessed 10 June 2021. Even as we speak, there are thousands of attacks on all aspects of the energy sector and the private sector, generally'.[1] Granholm's words were astounding because the US government has known for years that cyberattacks on key infrastructure were going on.